Increasing Students’ Numeracy Literacy Ability Through the Problem Based Learning Model - Nurrahmatullah, Nurrahmatullah (Indonesian Journal of Pedagogical and Social Sciences, 2024)
Abstract. This classroom action research aims to improve students' numeracy literacy skills by applying the problem-based learning model carried out in class XI.12 in the odd semester of the 2023/2024 academic year with a total of 36 students. This research was conducted in two cycles. Data was collected using the results of students' numeracy ability tests. The data obtained was collected and analyzed using descriptive statistical analysis, where the indicator of the success of this research was an increase in the N-Gain pretest-posttest value of students' numeracy abilities during each learning cycle. The research results showed that the N-Gain value of students' numeracy abilities in the first cycle was 0.35 in the medium category. In the second cycle, it increased to 0.72 in the high category. Thus, using the problem-based learning model can improve students' numeracy abilities. Keywords: Literasi, numerasi, problem based learning